2013
DOI: 10.1038/mi.2012.56
|View full text |Cite
|
Sign up to set email alerts
|

Re-utilization of germinal centers in multiple Peyer's patches results in highly synchronized, oligoclonal, and affinity-matured gut IgA responses

Abstract: Whereas gut IgA responses to the microbiota may be multi-centered and diverse, little is known about IgA responses to T-cell-dependent antigens following oral immunizations. Using a novel approach, gut IgA responses to oral hapten (4-hydroxy-3-nitrophenyl)acetyl-cholera toxin (NP-CT) conjugates were followed at the cellular and molecular level. Surprisingly, these responses were highly synchronized, strongly oligoclonal, and dominated by affinity matured cells. Extensive lineage trees revealed clonal relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
108
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(118 citation statements)
references
References 50 publications
6
108
1
3
Order By: Relevance
“…Overall, the IGHV repertoire that is used by TG2-specific PCs is limited and appears to be directed against a few epitopes of TG2. Dominant, expanded PC clones that are synchronized in inductive sites in the GALT are a feature of the intestinal IgA response to oral immunization with T cell-dependent Ags (42), and they were also described in healthy intestine (37). In this study, using the Hill diversity index, we not only demonstrate that TG2-specific PCs have a focused repertoire with low diversity, but we also show that among the TG2-specific PCs few clones dominate.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Overall, the IGHV repertoire that is used by TG2-specific PCs is limited and appears to be directed against a few epitopes of TG2. Dominant, expanded PC clones that are synchronized in inductive sites in the GALT are a feature of the intestinal IgA response to oral immunization with T cell-dependent Ags (42), and they were also described in healthy intestine (37). In this study, using the Hill diversity index, we not only demonstrate that TG2-specific PCs have a focused repertoire with low diversity, but we also show that among the TG2-specific PCs few clones dominate.…”
Section: Discussionmentioning
confidence: 80%
“…Intestinal IgA responses against T cell-dependent Ags usually evolve in germinal centers in gut-inductive sites and result in the formation of highly selected, affinity-matured PCs and long-lived memory cells (18,41,42). TG2-specific PCs likely develop with the help of T cells (12).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, by reutilizing several already existing CGs, antigen-specific B cells would be subjected to clonal expansion and SHM, as discussed previously (McHeyzer-Williams et al, 2011). This process apparently depends on persistent stimulation as it was shown to require antigen recall by multiple immunizations (Bergqvist et al, 2013).…”
Section: Immunological Memory and Mucosal Homeostasismentioning
confidence: 93%
“…Although mucosal IgA responses to commensal bacteria may be multicentered, of low affinity, and diverse, oral immunization of mice with a cholera toxin (CT)-adjuvanted novel antigen was shown to result in a strongly oligoclonal response of affinity-matured IgA + B cells (Bergqvist et al, 2013). Interestingly, it was found that the response was highly synchronized throughout the entire intestine by involving multiple PPs .…”
Section: Immunological Memory and Mucosal Homeostasismentioning
confidence: 98%
“…Previous studies demonstrated the usefulness of this method and resulted in new insights regarding differences in GC dynamics in aging or between different tissues [35]- [37],in autoimmune diseases [38], chronic inflammation [39], lymphomas [40], and chronic gastritis and gastric lymphomas [41]. This method was also used to determine clonal relationships of Ig genes from different tissues [39] [42].…”
Section: Introductionmentioning
confidence: 99%